1985
DOI: 10.1210/jcem-60-3-590
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Pituitary Desensitization and Prolongation of Gonadotropin Release by Estrogen during Continuous Administration of Gonadotropin-Releasing Hormone in Women: Its Antagonism by Progesterone*

Abstract: The present study was designed to elucidate gonadal steroid influences on gonadotropin release and subsequent pituitary desensitization to GnRH. Sixteen women, 10 of whom were normal and 6 of whom had hypogonadism, were infused with GnRH at rates ranging from 0.313-10 micrograms/h via an indwelling iv catheter for 66 h. Blood samples obtained throughout the GnRH infusion were analyzed for LH, FSH, estradiol, and progesterone. A prompt and substantial release of gonadotropin occurred in women with ovarian failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In rats oestrogen enhances the self-priming effect of GnRH (Aiyer, Chiappa & Fink, 1974) by acting on the pituitary and by increasing endogenous GnRH release (Speight, Popkin, Watts & Fink, 1981). Araki, Chikazawa, Motoyama et al (1985) found that pitui¬ tary desensitization during high-dose infusions of GnRH is less marked during the oestrogen-dominant, follicular phase of the menstrual cycle in women.…”
Section: Discussionmentioning
confidence: 99%
“…In rats oestrogen enhances the self-priming effect of GnRH (Aiyer, Chiappa & Fink, 1974) by acting on the pituitary and by increasing endogenous GnRH release (Speight, Popkin, Watts & Fink, 1981). Araki, Chikazawa, Motoyama et al (1985) found that pitui¬ tary desensitization during high-dose infusions of GnRH is less marked during the oestrogen-dominant, follicular phase of the menstrual cycle in women.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to a more distinct depletion of LH pool by triptorelin and the additional steroid treatment. Araki et al suggested that estradiol reduces pituitary desensitization and that the effects of estradiol are antagonized by progesterone [55]. Simard et al demonstrated that progesterone potentiates the inhibitory effect of estradiol on LH mRNA levels in male and female rats stimulated with triptorelin [56].…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the ability 1991; Parinaud et al, 1992;Jenkins et al, 1993). of progesterone to decrease gonadotrophin release in response There have been several reports on the presence of ovarian to GnRH agonist (Araki et al, 1985), therefore the initial cysts while the women are still undergoing treatment with transient 'flare-up effect' of GnRH agonist becomes subdued GnRH agonists (Feldberg et al, 1989;Ron-El et al, 1989; and subsequently the formation of cysts. This hypothesis Sampaio et al, 1991;Jenkins et al, 1992;Parinaud et al, explains the presence or formation of ovarian cysts after GnRH 1992; Stewart et al, 1992;Jenkins et al, 1993;Tarlatzis et al, agonist administration, but fails to explain how these 'cysts' 1994; Keltz et al, 1995;Weissman et al, 1998).…”
Section: Hypothesis Imentioning
confidence: 99%